Exploring the fingerprintability of honeypot systems, based on observed discrepancies, and designing and proposing techniques for preventing detection - Kyriakou, Stylianos (My University, 2025)
Cybersecurity is a crucial aspect of today's highly interconnected world. Nowadays, everything is connected to the internet, exposing a potentially broad surface to attacks, since everything is susceptible. From personal computers, to servers, cloud infrastructure, mobile devices, sensors, and even electrical appliances - almost every device we use in our daily life - is potentially vulnerable and susceptible to attacks, and is being attacked daily. One technology that has been designed and deployed to help us better understand how attackers and malicious actors act, is honeypots. Honeypots are decoy systems that aim to entrap attackers into thinking that they managed to gain access to a system but in reality, they are in a separate environment aimed at monitoring their behavior and letting the administrators know how an attacker is carrying out their attack, what vulnerabilities they might go after, and what tools or techniques they are using. This in the end can help the developers improve their system’s security. The problem arises when an attacker figures out that they are interacting with a honeypot - a process known as fingerprinting - and, as a result, they either avoid carrying out their attack or, in some cases, even turn the honeypot against its owner. This thesis aims to help make honeypots undetectable so they can spy on the attackers and let the developers know their system’s weakest links. By analyzing headers, banners, and service behaviors, and comparing them to those of real-world machines, I aim to suggest practical techniques that enhance the stealth and effectiveness of honeypots.
Keywords: Cybersecurity; internet